Hereditary angio-oedema with C1 inhibitor deficiency: Characteristics and diagnostic delay of Czech patients from one centre - Hakl, R; Kuklínek, P; Kadlecová, P; Litzman, J (Allergologia et immunopathologia, 2016)
BACKGROUND: Hereditary angio-oedema (HAE) is manifested by repeated episodes of localised subcutaneous or sub-mucosal oedema. Symptoms are extremely variable in frequency, localisation, and severity. Atypical or mild clinical symptoms of the disease may lead to erroneous diagnosis, causing diagnostic delay. The goal of this study was to assess how diagnostic delay has changed over 33 years at a single referral centre. METHODS: We analysed diagnostic delay and first symptoms of HAE in patients who were diagnosed at an immunology department between 1980 and 2013. Patient's records were analysed. RESULTS: The median diagnostic delay in 77 HAE type 1 and 2 patients was seven (range, 0-42) years. The difference observed in diagnostic delay between probands (18 [0-42] years) and others (1 [0-37] year) was significant (p<0.001). Our data show a significant negative correlation between the length of diagnostic delay and the year of diagnosis in our group of patients (p=0.024). The median age of first symptoms among all HAE patients (N=64) was 17 (1-40) years. The first symptoms of HAE in 64 patients were analysed. Twenty-six patients had abdominal, seventeen peripheral, five facial, two urogenital, and three had laryngeal oedema as the first manifestation of the disease. The last death that was attributed to HAE was in 1977. CONCLUSIONS: Our observations demonstrate improved awareness of HAE among physicians, as documented by the significant decrease in diagnostic delay. It is believed that earlier treatment will improve patient quality of life and life expectancy.
Keywords: Delayed Diagnosis; Retrospective Studies; opožděná diagnóza; kojenec; komplement C1 - inaktivátory; mladiství; Česká republika; mužské pohlaví; Infant; Diagnostic delay; First symptoms; Adult; mladý dospělý; Czech Republic; kvalita života; dítě; nefelometrie a turbidimetrie; Child; Complement C1 Inactivator Proteins; Child, Preschool; Young Adult; ženské pohlaví; inhibiční protein komplementu C1; retrospektivní studie; předškolní dítě; Humans; Complement C1 Inhibitor Protein; Nephelometry and Turbidimetry; Hereditary angio-oedema; dospělí; hereditární angioedémy; Female; Quality of Life; Adolescent; Angioedemas, Hereditary; lidé; Male